Accounting of Deformation Heating During Upsetting of AMg6 Alloy - Liudmila V. Radionova; Dmitry V. Gromov; Vitaly A. Bykov (Machines)
The AMg6 alloy, which belongs to the Al–Mg–Mn system, has high corrosion resistance in various environments, good weldability, and good mechanical properties. During analytical and experimental studies, it was established that the AMg6 alloy, when deformed in the temperature range of 130–175 °C, has high plastic properties and can withstand large degrees of deformation without destruction and crack formation. At the same time, its microstructure retains the texture of deformation, and the hardness of the alloy increases, which indicates its deformation hardening. The article presents the results of numerical and laboratory experiments on upsetting of 20 mm diameter workpieces from a heating temperature of 20, 130, 260 and 390 °C. Using numerical experiments, the dependences of deformation heating on the upsetting rate and the initial temperature of the workpiece were obtained. Deformation heating should be taken into account when choosing heating before deformation since it can be critical in terms of overburning and loss of plastic properties and corrosion resistance of finished products. The deformation behavior of the AMg6 alloy at a heating temperature of the workpiece up to 130–175 °C, revealed in this study, indicates the prospects for conducting additional research on the study of changes in the microstructure and mechanical properties of this alloy during warm deformation.